Macromolecular crystallography using microcrystal electron diffraction. Issue 3 (1st March 2021) - Clabbers, Max T. B.; Xu, Hongyi
Abstract : The current status and ongoing development of 3D electron diffraction and microcrystal electron diffraction in macromolecular crystallography are reviewed. Abstract : Microcrystal electron diffraction (MicroED) has recently emerged as a promising method for macromolecular structure determination in structural biology. Since the first protein structure was determined in 2013, the method has been evolving rapidly. Several protein structures have been determined and various studies indicate that MicroED is capable of (i) revealing atomic structures with charges, (ii) solving new protein structures by molecular replacement, (iii) visualizing ligand‐binding interactions and (iv) determining membrane‐protein structures from microcrystals embedded in lipidic mesophases. However, further development and optimization is required to make MicroED experiments more accurate and more accessible to the structural biology community. Here, we provide an overview of the current status of the field, and highlight the ongoing development, to provide an indication of where the field may be going in the coming years. We anticipate that MicroED will become a robust method for macromolecular structure determination, complementing existing methods in structural biology.